Situation and Solutions for Tourism Development in the New Normal: A Case Study in Da Lat City, Vietnam - Hien, Vo Ngoc (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
Tourism is one of the important human needs, and it is becoming more and more essential when the quality of life of Vietnamese people, in general, is increasing significantly. The desire to visit and experience new lands with a cool, fresh climate and beautiful nature like Da Lat city is increasing, especially when the COVID-19 pandemic has kept many people for quite a while. When the new normal state was established in many provinces and Da Lat city, many tourists chose this place as their first destination after many days of living and working at home, in areas with hot and smoky climates such as in large cities lowlands of Vietnam. This research paper is completed from comparative and comparative studies, past and present documents, and a combination of surveys and actual interviews. Research results show that tourists' satisfaction level when traveling in Da Lat city during the new normal period is generally relatively low because of worries about being adversely affected by the pandemic. Meanwhile, the need to return to this tourist destination is very high, of course, when everything has been remedied to create a safer destination. This opens up the massive potential for tourism of Da Lat city in the coming period.